Ghostbusters. - Reitman, Ivan; Murray, Bill, 1950 September 21-; Aykroyd, Dan; Weaver, Sigourney, 1949-; Ramis, Harold; Moranis, Rick (Culver City, Calif. : Columbia Pictures : Sony Pictures Home Entertainment, 2005)
Three former parapsychology professors set up shop as a unique ghost removal service.
Special features: filmmakers' commentary; behind-the-scenes featurettes.
new dvd 2022 spring.
Music, Elmer Bernstein.
English, French or Spanish dialogue, English, French, Spanish, Portuguese, Chinese, Korean or Thai subtitles.
Translated from English ; Parallel text in French ; Parallel text in Spanish.
Parallel text in French ; Parallel text in Spanish ; Translated from English.
Keywords: National Film Registry; Comedy films